Fig. 1 in Helminths Of Wild Predatory Mammals Of Ukraine. Nematodes - Varodi, E. I.; Malega, A. M.; Kuzmin, Y. I.; Kornyushin, V. V. (Zenodo, 2017)
Fig. 1. Structure of nematode communities in carnivorans of the family Canidae in Ukraine (based on original data). A — red fox; B — wolf; C — raccoon dog. Toxe — Toxascaris leonina; Unst — Uncinaria stenocerhala; Toca — Toxocara canis; Pepl — Pearsonema plica; Euae — Eucoleus aeropilus; Paff — Pterygodermatites affinis; Trvu — Trichuris vulpis; Mopa — Molineus patens; Crvu — Crenosoma vulpis; Casp — Capillaria sp.; Ster — Strongyliodes erschowi; Spar — Spirocerca artica; Splu — S. lupi; Trsp — Trichinella cf. spiralis; Aopu — Aonchotheca putorii; Syag — Sy. agraria; Heum — Heligmosomum sp.; Anca — Ancylostoma caninum. Published as part of Varodi, E. I., Malega, A. M., Kuzmin, Y. I. & Kornyushin, V. V., 2017, Helminths Of Wild Predatory Mammals Of Ukraine. Nematodes, pp. 187-202 in Vestnik Zoologii 51 (3) on page 194, DOI:10.1515/vzoo-2017-0026, http://zenodo.org/record/6454176